Chứng minh rằng :
D=\(\sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6++...+\sqrt[3]{6}}}}< 2\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Cho \(A=\sqrt{6+\sqrt{6...+\sqrt{6}}+\sqrt[3]{6+\sqrt[3]{6...+\sqrt[3]{6}}}}\) Chứng minh rằng 4<A<5
Cho \(A=\sqrt{6+\sqrt{6...+\sqrt{6}}+\sqrt[3]{6+\sqrt[3]{6...+\sqrt[3]{6}}}}\) Chứng minh rằng 4<A<5
a) ta có 2√5= = √20 ; 3√2 =
= √ 18 => 2√5 > 3√2
=> <
b) 6√3 = = √108 ; 3√6 =
= √54 => 6√3 > 3√6 =>
>
a) \(2\sqrt{5}=\sqrt{2^2.5}=\sqrt{20}\)
\(3\sqrt{2}=\sqrt{3^2.2}=\sqrt{18}\)
=> \(2\sqrt{5}>3\sqrt{2}\)
=> \(\left(\dfrac{1}{3}\right)^{2\sqrt{5}}< \left(\dfrac{1}{3}\right)^{3\sqrt{2}}\)
(vì cơ số \(\dfrac{1}{3}< 1\))
b) Vì \(3< 6^2\)
=> \(3^{\dfrac{1}{6}}< \left(6^2\right)^{\dfrac{1}{6}}\)
=> \(\sqrt[6]{3}< 6^{\dfrac{1}{3}}\)
=> \(\sqrt[6]{3}< \sqrt[3]{6}\)
=> \(7^{\sqrt[6]{3}}< 7^{\sqrt[3]{6}}\)
\(\sqrt{7}-\sqrt{3}=\frac{4}{\sqrt{7}+\sqrt{3}}< \frac{4}{\sqrt{6}+\sqrt{2}}=\sqrt{6}-\sqrt{2}.\)
\(\frac{3}{2}\sqrt{6}+2\sqrt{\frac{2}{3}}-4\sqrt{\frac{3}{2}}=\frac{3}{2}\sqrt{6}+\frac{2.1}{3}\sqrt{2.3}-\frac{4.1}{2}\sqrt{3.2}\)
\(=\frac{3}{2}\sqrt{6}+\frac{2}{3}\sqrt{6}-2\sqrt{6}=\sqrt{6}\left(\frac{3}{2}+\frac{2}{3}-2\right)\)
\(=\sqrt{6}\left(\frac{9}{6}+\frac{4}{6}-\frac{12}{6}\right)=\sqrt{6}.\frac{1}{6}=\frac{\sqrt{6}}{6}\)
Vậy \(\frac{3}{2}\sqrt{6}+2\sqrt{\frac{2}{3}}-4\sqrt{\frac{3}{2}}=\frac{\sqrt{6}}{6}\)
\(D=\sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{6+\sqrt[3]{6}}}}}\)
\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{6+\sqrt[3]{8}}}}}\)
\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{6+2}}}}\)
\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{6+\sqrt[3]{6+...+\sqrt[3]{8}}}}\)
\(\Rightarrow D< \sqrt[3]{6+\sqrt[3]{8}}=\sqrt[3]{6+2}=\sqrt[3]{8}\)
\(\Rightarrow D< 2\) (đpcm)